Settlements in the Supreme Court of Israel - David Kretzmer (AJIL Unbound, 2017)
One of the unique features of Israel's legal, military, and political control over the Occupied Palestinian Territories (OPT) has been the review by the Supreme Court of Israel of the actions and decisions of the authorities in those territories. Sitting as a High Court of Justice that has the competence to review the actions of all persons exercising public functions under law, the Court has entertained thousands of petitions relating to the legality of such varied actions as house demolitions, deportations, land requisition, entry permits, and establishment of settlements. There can be little doubt that the very existence of judicial review has had a restraining effect on the authorities. While the Court has not ruled against the government that often, and has provided legitimization for acts of dubious legality, such as punitive house demolitions and deportations, it has handed down some important rulings on questions of principle. Furthermore, in the shadow of the Court, many petitions have been settled without a court ruling, allowing for a full or partial remedy for the Palestinian petitioner.